2018
DOI: 10.1002/hbm.24377
|View full text |Cite
|
Sign up to set email alerts
|

Reward‐related regions form a preferentially coupled system at rest

Abstract: Neuroimaging studies have implicated a set of striatal and orbitofrontal cortex (OFC) regions that are commonly activated during reward processing tasks. Resting‐state functional connectivity (RSFC) studies have demonstrated that the human brain is organized into several functional systems that show strong temporal coherence in the absence of goal‐directed tasks. Here we use seed‐based and graph‐theory RSFC approaches to characterize the systems‐level organization of putative reward regions of at rest. Peaks o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 89 publications
(134 reference statements)
3
15
0
Order By: Relevance
“…The mPFC has been recognized as one of the key brain regions comprising the reward neural circuitry (Dillon et al, ; Haber & Knutson, ; Huckins et al, ; Izuma et al, ). It plays an important role in encoding the probability and/or the value of a reward (Gläscher et al, ; Hu, ; Rushworth et al, ; Samejima & Doya, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mPFC has been recognized as one of the key brain regions comprising the reward neural circuitry (Dillon et al, ; Haber & Knutson, ; Huckins et al, ; Izuma et al, ). It plays an important role in encoding the probability and/or the value of a reward (Gläscher et al, ; Hu, ; Rushworth et al, ; Samejima & Doya, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the modulated neural activities in the reward circuitry are found to be associated with reward‐related behaviors, such as the processing of rewarding music (Seminowicz et al, ) and the analgesic effect of placebo (Yu et al, ). In detail, brain areas in the reward neural circuitry are known to include the nucleus accumbens (NAcc) in the ventral striatum, the medial prefrontal cortex (mPFC), the orbital prefrontal cortex, and the anterior cingulate cortex (Dillon et al, ; Haber & Knutson, ; Huckins et al, ; Izuma, Saito, & Sadato, ). Studies with experimental acute pain found that, both the mPFC activity and its functional connectivity with NAcc were enhanced when subjective pain intensity was self‐regulated (Woo, Roy, Buhle, & Wager, ).…”
Section: Introductionmentioning
confidence: 99%
“…We selected eight nodes in the frontoparietal control network to remain consistent with our prior work showing that aggregate activity across these 8 nodes, versus activity in a larger set of frontoparietal nodes, was most predictive of dieters' self-control success and failure in daily life (Lopez et al, 2017). However, in order to investigate whether this effect generalizes across a larger set of nodes we used 31 frontoparietal nodes from a recently published parcellation study within our group based on a large, independent sample (N=828; Huckins et al, 2019) to re-compute regulation-reward balance scores. The findings presented in the main text largely replicated (for more details see Supplementary Materials for all results from this analysis).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 60%
“…We selected eight nodes in the frontoparietal control network to remain consistent with our prior work showing that aggregate activity across these eight nodes, versus activity in a larger set of frontoparietal nodes, was most predictive of dieters’ self-control success and failure in daily life (Lopez et al, 2017). However, in order to investigate whether this effect generalizes across a larger set of nodes we used 31 frontoparietal nodes from a recently published parcellation study within our group based on a large, independent sample ( N = 828; Huckins et al, 2019) to re-compute regulation–reward balance scores. The findings presented in the main text largely replicated (for more details see Supplementary Materials for all results from this analysis).…”
Section: Methodsmentioning
confidence: 99%